Cryo-EM structure of Helicobacter pylori urease with an inhibitor in the active site at 2.0 Å resolution - Eva S. Cunha (Nature Portfolio, 2021)
Infection by Helicobacter pylori is associated with peptic ulcers and gastric cancer. H. pylori urease is required for colonization of the stomach and thus an attractive antimicrobial drug target. Cryo-EM analyses of the H. pylori urease with inhibitors bound reveal structural details useful in rational drug design.